Antibacterial activity in fish mucus from farmed fish - Mozumder, Mohammad Mojibul Hoque (Universitetet i Tromsø, 2005)
Mucus samples were collected from five different farmed Atlantic salmon (Salmo salar) and Atlantic cod (Gadus morhua) in order to study the content of antibacterial activity in the mucus and to compare the activity of mucus samples of the two different fish species. The mucus samples were diluted in buffer, desalted and adjusted to different protein concentrations in the mucus samples, A search for antibacterial activity in the mucus was performed for different protein concentrations, against four different bacterial strains Escherichia coli, Listionella anguillarum, Corynebacterrium glutamicum and Staphylococcus aureus.Protein concentrations in cod mucus samples were found higher than the salmon mucus samples when tested by different protein assays, Bicinchonic assay (BCA) and absorbance based method with measurement in spectrophotometer at A280 nm. Antibacterial activity was detected in mucus samples of both fish species, against the four bacterial strains. The bacteria C. glutamicum was the most sensitive, while S. aureus was the least sensitive against the different mucus samples. Furthermore, mucus samples of cod contained more antibacterial active substances than the mucus samples of the salmon. The results of this study indicate that that the mucus of salmon and cod contain one or several components with antibacterial activity. These bioactive substances may play an important role in the ability of mucus to defend salmon and cod against pathogenic bacteria or microorganisms. However, more investigation is necessary to confirm the antibacterial activity in cod and salmon mucus and to purify and characterize the active components.